Dynamic response assessment of an offshore wind turbine under Peruvian environmental conditions - Barreto, D. (2023)
This paper presents a dynamic response analysis of an offshore monopile wind turbine to be deployed at a near-shore area in the south-centre part of the Peruvian coast (Marcona). It is a 5 MW three bladed wind turbine that operates in an aggressive offshore environment described by its stochastic behaviour. Thus it is necessary to use a statistical approach for its characterization. The operating wind turbine is simulated using an aero-hydro-servo-elastic computational tool (FAST) that allows the simulation of coupled systems. After the simulation, this work analyses relevant dynamic responses (thrust, torque, shear forces, and bending moments). Time series of these responses at critical zones of the wind turbine are presented. The results indicate high variability of the responses and critical fluctuations located at the mudline. It is found that this variability is due to the additional dynamic loads coming from the ocean waves. This is a big issue to consider when designing a monopile offshore wind turbine operating under the Peruvian environmental conditions.